(untitled) (Research Data Journal for the Humanities and Social Sciences, 2024)
In genetic criticism, scholarly editing, authorial philology and, more generally, for the study of authorial manuscripts and writing processes, it is essential to order and classify the textual witnesses and their relationships. This article presents two datasets of so-called ‘genetic networks’, that is representation of the genetic entities (witnesses, publications, dossiers) and their relationships, modelled according to the geno 1.0 ontology. The datasets contain genetic networks of the works of two Swiss authors: the main publications of Gustave Roud (1897–1976) and the short story “En mer” by Bernard Comment (1960).